Complete Genome Sequence of the Novel Duck Circovirus Strain GH01 from Southwestern China - Zhang, Zhilong (American Society for Microbiology, 2013)
A novel duck circovirus (DuCV) strain, designated GH01, was isolated from ducklings in southwestern China. We report the genome sequence of GH01 and the genomic organization and genetic relationship to other DuCVs. The availability of the genome sequence will be helpful to investigations of epidemiology and the evolutionary biology of this organism and the development of preventive vaccines.